2019
DOI: 10.3390/ijerph16071263
|View full text |Cite
|
Sign up to set email alerts
|

Association between Regular Electronic Nicotine Product Use and Self-Reported Periodontal Disease Status: Population Assessment of Tobacco and Health Survey

Abstract: Electronic nicotine product use is increasing in the U.S., but few studies have addressed its effects on oral health. The goal of this work was to determine the association between electronic nicotine product use and periodontal disease. Population Assessment of Tobacco and Health adult survey data from 2013–2016 (waves 1, 2 and 3) was used for the analysis. Longitudinal electronic nicotine product users used electronic nicotine products regularly every day or somedays in all three waves. Participants with new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 34 publications
2
44
0
2
Order By: Relevance
“…In vitro studies have shown that e-cig aerosols can have detrimental effects on gingival epithelial cells and periodontal fibroblasts [ 31 ]. Although a cross-sectional study did not find significantly worse periodontal conditions in e-cig users than in never smokers [ 32 ], a recent study revealed that e-cig users have a higher risk of being diagnosed with gum disease and periodontal bone loss compared to subjects who have never used electronic nicotine delivery systems [ 33 ].…”
Section: The Link Between Periodontal Diseases and Systemic Conditmentioning
confidence: 99%
“…In vitro studies have shown that e-cig aerosols can have detrimental effects on gingival epithelial cells and periodontal fibroblasts [ 31 ]. Although a cross-sectional study did not find significantly worse periodontal conditions in e-cig users than in never smokers [ 32 ], a recent study revealed that e-cig users have a higher risk of being diagnosed with gum disease and periodontal bone loss compared to subjects who have never used electronic nicotine delivery systems [ 33 ].…”
Section: The Link Between Periodontal Diseases and Systemic Conditmentioning
confidence: 99%
“…Gingival pain was also reported more often by combustible cigarette smokers than by e‐cigarette users. However, although periodontal inflammation and self‐perceived oral symptoms were higher with cigarette smoke, it should be noted that e‐cigarettes also contributed to adverse periodontal health for their users as compared with non‐smokers (Atuegwu et al., 2019). The presence of humectants (propylene glycol (PG) and glycerol (GLY)) gives e‐liquid its high viscosity, which may promote its adherence to exposed surfaces, such as the soft and hard tissues of the oral cavity, as well as dental restoration materials.…”
Section: Introductionmentioning
confidence: 99%
“…The long-term effects of e-cigarette use remain largely unknown, but e-cigarette aerosols contain toxins that can affect health [ 5 , 6 , 7 , 8 ]. There is increasing evidence that e-cigarettes may be associated with an increased risk of oral diseases [ 9 , 10 ], prediabetes [ 11 ], depression [ 12 , 13 ], asthma, chronic obstructive pulmonary disease (COPD) and respiratory symptoms [ 14 , 15 , 16 , 17 , 18 ]. Recently, the Centers for Disease Control and Prevention (CDC) reported multiple cases of e-cigarette or vaping product use-associated lung injury (EVALI), some of which resulted in deaths [ 19 ].…”
Section: Introductionmentioning
confidence: 99%